A Reconceptualization of General and Specific Deterrence - Stafford, Mark C. (Journal of research in crime and delinquency, 1993)
The distinction between general and specific deterrence is widely recognized and accepted by deterrence researchers, and is used commonly to classify deterrence studies. However; the logical and empirical grounds for the distinction are not as clear as they might appear; and the conventional conception has done more to obfuscate than to clarify the deterrence process. Following a discussion of these issues, the authors propose a reconceptualization of general and specific deterrence, and apply it to several current controversies in the deterrence literature. [ABSTRACT FROM AUTHOR]